Advancing healthcare through piezoresistive pressure sensors: a comprehensive review of biomedical applications and performance metrics - Mokhalad Alghrairi; Basim Abdul Kareem Farhan; Hussein Mohammed Ridha; Saad Mutashar; Waleed Algriree; Bayan Mahdi Sabbar (Journal of Physics Communications, 2024)
Piezoresistive pressure sensors have transformed biomedical applications, enabling precise diagnostics and monitoring. This concise review explores the fundamental principles, key components, and fabrication techniques of piezoresistive pressure sensors, focusing on critical performance metrics such as sensitivity, accuracy, and response time. Biomedical design challenges, including biocompatibility and long-term stability, are examined, offering insights into solutions for optimal sensor integration. In diverse biomedical applications, piezoresistive pressure sensors play pivotal roles, from blood pressure monitoring to implantable medical devices. The paper emphasizes their versatility in enhancing patient care through continuous and accurate monitoring. Looking forward, the review discusses emerging trends and potential research directions, positioning piezoresistive pressure sensors as central contributors to the future of biomedical technology, promising improved patient outcomes and advanced healthcare delivery through precise and continuous monitoring.